Electro‐Reconfigurable Adaptive Microlens with Simultaneous Multidirectional Focal Adjustment and Zooming (Adv. Mater. Technol. 8/2023). Issue 8 (24th April 2023) - Yoon, Jae Uk; Han, Dong‐Heon; Oh, Seung‐Ju; Woo, Insun; Park, Hyeon‐Su; Bae, Jin Woo
Abstract : Adaptive Microlens In article number 2201988, Jin Woo Bae and co‐workers present a PVC gel‐based electro‐reconfigurable adaptive microlens that enables multidirectional focal adjustment and zooming without mechanical parts or fluid leakage like human eyes. It has an excellent variable focal length at low input voltages, high transparency, and fast response, showing great potential for future electric optical modules.